2006
DOI: 10.1152/ajpheart.00484.2006
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial coordination of cerebral vasomotion via myoendothelial gap junctions containing connexins 37 and 40

Abstract: Control of cerebral vasculature differs from that of systemic vessels outside the blood-brain barrier. The hypothesis that the endothelium modulates vasomotion via direct myoendothelial coupling was investigated in a small vessel of the cerebral circulation. In the primary branch of the rat basilar artery, membrane potential, diameter, and calcium dynamics associated with vasomotion were examined using selective inhibitors of endothelial function in intact and endothelium-denuded arteries. Vessel anatomy, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 53 publications
(94 reference statements)
6
118
1
Order By: Relevance
“…E, MEGJs are ϳ12-fold higher in density in obese compared with control. As found previously for some MEGJ-associated projections in rat caudal cerebellar and mesenteric artery (Sandow et al, 2002Haddock et al, 2006), the endothelial "head" of such MEGJ-associated projections is multilobed (examples with asterisks, A and B); perhaps providing greater surface area for localized Ca 2ϩ and K ϩ channel activity compared with nonlobed projections. Such sites have characteristic pentalaminar MEGJ morphology (arrows and insets) and apparent localized IK Ca (IK1) densities (Fig.…”
Section: Downloaded Fromsupporting
confidence: 67%
See 2 more Smart Citations
“…E, MEGJs are ϳ12-fold higher in density in obese compared with control. As found previously for some MEGJ-associated projections in rat caudal cerebellar and mesenteric artery (Sandow et al, 2002Haddock et al, 2006), the endothelial "head" of such MEGJ-associated projections is multilobed (examples with asterisks, A and B); perhaps providing greater surface area for localized Ca 2ϩ and K ϩ channel activity compared with nonlobed projections. Such sites have characteristic pentalaminar MEGJ morphology (arrows and insets) and apparent localized IK Ca (IK1) densities (Fig.…”
Section: Downloaded Fromsupporting
confidence: 67%
“…In this regard, in addition to gap junction effects, carbenoxolone and Gap peptides have nongap junction vascular ion channel and putative calcium store activity (Coleman et al, 2001;Tare et al, 2002;Haddock et al, 2006;Dora et al, 2008). Indeed, volume-regulated anion channel block with carbenoxolone mimics Cx43 block in astroglial cells (Benfenati et al, 2009), in a similar manner to its action in rat mesenteric artery (compare carbenoxolone data and interpretation in Tare et al, 2002;Dora et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gap peptides have been shown to inhibit the hyperpolarisation induced by endothelium-dependent vasodilators in rat mesenteric [39] and saphenous [6] arteries, and inhibit relaxations to acetylcholine in rabbit central ear arteries [40]. Additionally, gap peptides have been shown to abolish gap junctionmediated vasomotion in rat basilar arteries [41]. Studies have also shown that some tissues require a combination of gap peptides to cause significant attenuation of the relaxation response [10], with individual peptides observed to have either no or negligible effects.…”
Section: Discussionmentioning
confidence: 99%
“…The arteries were mounted in DAPI and coverslip sealed to provide a flat surface for confocal imaging. Autofluorescence of the internal elastic lamina between the endothelium and smooth muscle was readily apparent with "holes" between the two layers of cells which has been extensively documented (e.g., [212][213][214]). In our study, the detection of punctate fluorescence in >25% of the "holes" was considered indicative of protein localization to MEJs.…”
Section: Experimental Methodologies In the Study Of CX And Panx Functmentioning
confidence: 98%